Trends in seroprevalence of enteric transmitted hepatitis virus infections at a tertiary care hospital in Delhi: a 4-year review - Panda, Arpita; Jothi J., Belinda; Yadav, Pooja; Kumar, Shilpee (International Journal Of Community Medicine And Public Health, 2023)
Background: Hepatitis A virus (HAV) and hepatitis E virus (HEV), both enteric hepatitis viruses, are transmitted through the feco-oral route. These infections can range from asymptomatic or subclinical cases to acute viral hepatitis, occasionally leading to mortality. To gain an understanding of the disease and develop effective management strategies, comprehending the disease burden is essential. This study aimed to provide insights into the prevalence of enteric transmitted hepatitis viruses among individuals with acute hepatitis in the Delhi region. Methods: A retrospective investigation was conducted at a prominent tertiary care super specialty hospital in Delhi, spanning from February 2019 to December 2022. Serum samples from patients suspected of having hepatitis and sent for HAV and HEV testing were included. The samples underwent enzyme-linked immunosorbent assay to detect HAV and HEV immunoglobulin (Ig)M antibodies. Collected data was analyzed using SPSS software version 21, employing Chi-square and Fischer exact tests where applicable. Results: Throughout the study period, a total of 1275 samples were incorporated. Viral etiology was evident in 197 patients (15.45%). Among these, IgM HAV was identified in 142 patients (11.13%), and IgM HEV was present in 55 patients (4.31%). HAV infection was notably more prevalent in the pediatric age group (20.89% or 89/426; p<0.001), while HEV was significantly more common among adolescents and adults (5.77% or 49/849; p<0.001). Conclusions: Regular surveillance of enteric transmitted viruses causing hepatitis should encompass both hospital and community levels to accurately gauge disease burden and evolving epidemiology.